Transient silencing of hypermutation preserves B cell affinity during clonal bursting - Juhee Pae; Niklas Schwan; Bertrand Ottino-Loffler; William S. DeWitt; Amar Garg; Juliana Bortolatto; Ashni A. Vora; Jin-Jie Shen; Alvaro Hobbs; Tiago B. R. Castro; Luka Mesin; Frederick A. Matsen; et al. (Nature, 2025)
Abstract In the course of antibody affinity maturation, germinal centre (GC) B cells mutate their immunoglobulin heavy- and light-chain genes in a process known as somatic hypermutation (SHM)1–4. Panels of mutant B cells with different binding affinities for antigens are then selected in a Darwinian manner, which leads to a progressive increase in affinity among the population5. As with any Darwinian process, rare gain-of-fitness mutations must be identified and common loss-of-fitness mutations avoided6. Progressive acquisition of mutations therefore poses a risk during large proliferative bursts7, when GC B cells undergo several cell cycles in the absence of affinity-based selection8–13. Using a combination of in vivo mouse experiments and mathematical modelling, here we show that GCs achieve this balance by strongly suppressing SHM during clonal-burst-type expansion, so that a large fraction of the progeny generated by these bursts does not deviate from their ancestral genotype. Intravital imaging and image-based cell sorting of a mouse strain carrying a reporter of cyclin-dependent kinase 2 (CDK2) activity showed that B cells that are actively undergoing proliferative bursts lack the transient CDK2low ‘G0-like’ phase of the cell cycle in which SHM takes place. We propose a model in which inertially cycling B cells mostly delay SHM until the G0-like phase that follows their final round of division in the GC dark zone, thus maintaining affinity as they clonally expand in the absence of selection.